2016
DOI: 10.7717/peerj.1998
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal ofPolyptychodon(Plesiosauria) from the Cretaceous of England

Abstract: Pliosauridae is a globally distributed clade of aquatic predatory amniotes whose fossil record spans from the Lower Jurassic to the Upper Cretaceous. However, the knowledge of pliosaurid interrelationships remains limited. In part, this is a consequence of a few key taxa awaiting detailed reassessment. Among them, the taxon Polyptychodon is of special importance. It was established on isolated teeth from the mid-Cretaceous strata of East and South East England and subsequently associated with numerous finds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 54 publications
2
58
0
1
Order By: Relevance
“…A recent reappraisal by Madzia (2016) showed, however, that the original material attributed to P. interruptus is most likely too variable to belong to a single taxon. This conclusion was further regarded as being supported by the considerable time span between the oldest and youngest specimens assigned to P. interruptus, likely to exceed 35 Ma (early Aptian to ?middle Santonian).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent reappraisal by Madzia (2016) showed, however, that the original material attributed to P. interruptus is most likely too variable to belong to a single taxon. This conclusion was further regarded as being supported by the considerable time span between the oldest and youngest specimens assigned to P. interruptus, likely to exceed 35 Ma (early Aptian to ?middle Santonian).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the material was attributed to the taxon Polyptychodon Owen, 1841a. However, a recent reappraisal of the original material of P. interruptus Owen, 1841b showed that the teeth associated with the taxon do not bear any autapomorphies and most likely belonged to different species or possibly even members of different larger clades (Madzia 2016). As a result, it was recommended that other specimens attributed to P. interruptus should be reconsidered as well.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations